Preparation method of high-compatibility nano calcium carbonate

CN122668442BActive Publication Date: 2026-10-20山东宇信纳米科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611149108.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-20
Estimated Expiration
2046-07-31

AI Technical Summary

Technical Problem

[0005]本发明针对现有技术中存在的问题,提供了一种高相容性纳米碳酸钙的制备方法,采用分步化学键合构建致密内层,辅以物理润滑外层,形成双层分散机制,解决纳米碳酸钙表面极性高易团聚、单层偶联剂包覆界面结合强度不足、高填充下加工性能与增韧效果难以兼顾的技术难题

Benefits of technology

通过六偏磷酸钠、乙二醇与乳酸三元复配晶型控制剂的协同调控,在碳化阶段即可获得粒径均一、分散良好的纳米碳酸钙初级粒子,为后续表面改性提供理想的基材条件。通过偶联剂与硬脂酸的分步化学改性,在纳米碳酸钙表面构建了致密、稳定的化学键合层,克服了传统单层包覆不完整、界面结合强度不足的缺陷。改性后的纳米碳酸钙由亲水性转变为疏水性,活化度高,与PE基体的界面相容性显著改善。通过柠檬酸三丁酯与PE蜡的复合物理润滑包覆,在化学键合层之外构建了润滑性外层,建立了化学键合与物理润滑双重分散机制,确保纳米碳酸钙在母粒制备及后续薄膜成型过程中始终保持纳米尺度均匀分布,即使在高填充量下,仍能保持良好的熔体流动速率和加工流动性,避免因填充过高导致的加工困难或分散不均。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of nano calcium carbonate, in particular to a preparation method of high-compatibility nano calcium carbonate, which comprises the following steps: firstly, regulating the carbonation process by a ternary compound crystal form control agent of sodium hexametaphosphate, ethylene glycol and lactic acid to obtain nano calcium carbonate with uniform particle size; then, sequentially performing step-by-step chemical bonding modification with a coupling agent and stearic acid to build an inner layer of chemical bonding interface; and finally, performing composite physical lubrication coating with tributyl citrate and PE wax to build an outer layer of physical lubrication layer. Through the dual dispersion mechanism of chemical bonding and physical lubrication, the present application realizes the uniform dispersion of nano calcium carbonate in the PE matrix, and at the same time, the processing fluidity and the toughening and reinforcing effect are considered under high filling amount, which is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nano-calcium carbonate technology, and in particular to a method for preparing highly compatible nano-calcium carbonate. Background Technology

[0002] Nano-calcium carbonate, as an important inorganic filler, has advantages such as wide availability, low cost, and non-toxicity and odorlessness, and is widely used in plastics, rubber, coatings, inks and other fields. In the toughening and modification of polyethylene (PE), filling nano-calcium carbonate into the PE matrix can significantly improve the impact resistance and puncture resistance of the composite material, while reducing material costs.

[0003] Nano-calcium carbonate has a large number of hydroxyl groups on its surface, making it highly hydrophilic, while the PE matrix is ​​a non-polar hydrophobic polymer material, resulting in a significant difference in their interfacial properties. When unmodified nano-calcium carbonate is directly filled into PE, the particles agglomerate severely due to strong van der Waals forces and electrostatic forces, making it difficult to achieve uniform dispersion at the nanoscale. This not only fails to exert the toughening and reinforcing effect of nanoparticles but also creates stress concentration points in the composite material, leading to a deterioration in mechanical properties.

[0004] In existing technologies, titanate coupling agents or stearic acid are typically used to perform a single surface modification treatment on nano-calcium carbonate. Single-layer coating often suffers from problems such as incomplete coating and uneven coating layer. During the composite process of modified nano-calcium carbonate with PE matrix, the interface layer is easily damaged, resulting in insufficient interfacial bonding strength, which affects the toughening effect and service life of the composite material. Summary of the Invention

[0005] This invention addresses the problems existing in the prior art by providing a method for preparing highly compatible nano-calcium carbonate. It employs a stepwise chemical bonding to construct a dense inner layer, supplemented by a physical lubrication outer layer, forming a double-layer dispersion mechanism. This solves the technical challenges of nano-calcium carbonate having high surface polarity and easy agglomeration, insufficient interfacial bonding strength of single-layer coupling agent coating, and difficulty in simultaneously achieving processing performance and toughening effect under high filling conditions.

[0006] To solve the above-mentioned technical problems, the present invention includes the following steps: S1. Add nano-calcium carbonate powder to water, stir and mix to prepare a slurry with a solid content of 15% to 40%, and adjust the pH value of the slurry to 8 to 9 with NaOH aqueous solution to obtain nano-calcium carbonate slurry; S2. Add the coupling agent to 1 to 3 times its volume of anhydrous ethanol, stir and mix to obtain a diluted coupling agent solution; S3. Add the prepared coupling agent dilution to the nano-calcium carbonate slurry in the form of a spray. The addition time is controlled at 20-40 minutes. After the addition is completed, raise the system temperature to 60-80℃ and keep it at the temperature while stirring for 60-90 minutes to complete the first modification. S4. After the first modification is completed, liquid stearic acid is slowly added dropwise to the reaction system over a period of 15 to 30 minutes. After the addition is complete, the mixture is kept warm and stirred for 50 to 60 minutes to complete the second modification. S5. After the modification is completed, the slurry is naturally cooled to room temperature, centrifuged, the solids are collected, washed and dried, and the dried block powder is crushed and sieved to obtain modified nano calcium carbonate powder. S6. Add tributyl citrate to the modified nano-calcium carbonate powder in the form of spray, stir and mix for 5 to 15 minutes, add PE wax, mix at a temperature of 90 to 100°C for 10 to 30 minutes to obtain composite modified nano-calcium carbonate powder. S7. The modified powder is heated to 110-130℃ and cured at a constant temperature for 20-60 minutes. It is then naturally cooled to room temperature, deagglomerated by an air jet mill, and sieved to obtain the highly compatible modified nano-calcium carbonate product.

[0007] Preferably, the nano-calcium carbonate powder comprises the following preparation steps: (1) Limestone is crushed, calcined, digested, aged and filtered to obtain Ca(OH)2 slurry; (2) Pump Ca(OH)2 slurry into the carbonization kettle, add crystal form control agent, start stirring, control the temperature at 20-25℃, and introduce CO2 / N2 mixed gas to carry out carbonization reaction; (3) Carbonize the system until the pH drops to 7-8, stop the gas supply, keep it at a constant temperature for 20-40 minutes, and then carry out a second carbonization for 5-15 minutes to obtain calcium carbonate slurry; (4) After the calcium carbonate slurry has been aged, it is centrifuged and the solids are collected and then vacuum dried. The dried blocky powder is deagglomerated by airflow to obtain nano calcium carbonate powder.

[0008] Preferably, the coupling agent is a composite coupling agent composed of silane coupling agent and titanate coupling agent in a mass ratio of 1:1 to 2, and the total amount of the composite coupling agent is 2% to 3.5% of the mass of the nano-calcium carbonate powder.

[0009] Preferably, the amount of stearic acid used is 2% to 4% of the mass of the nano-calcium carbonate powder.

[0010] Preferably, the amount of tributyl citrate is 1% to 3% of the mass of the nano-calcium carbonate powder, and the amount of PE wax is 1% to 5% of the mass of the nano-calcium carbonate powder.

[0011] Preferably, the crystal form control agent is a mixed crystal form control agent composed of sodium hexametaphosphate, ethylene glycol and lactic acid in a mass ratio of 1-3:0.5-1.5:0.5-1, and the total amount of the mixed crystal form control agent is 0.5%-3.5% of the dry basis mass of Ca(OH)2 slurry.

[0012] Preferably, the volume ratio of CO2 to N2 in the CO2 / N2 mixed gas is 1:1 to 2.

[0013] Preferably, the total ventilation flow rate of the CO2 / N2 mixed gas is stably controlled at 36-48 m³ / h. 3 / min.

[0014] Preferably, the mass concentration of the Ca(OH)2 slurry is 6% to 10%.

[0015] After adopting the above technical solution, the beneficial effects of the present invention are: Through the synergistic regulation of a ternary composite crystal form control agent consisting of sodium hexametaphosphate, ethylene glycol, and lactic acid, uniformly sized and well-dispersed primary nano-calcium carbonate particles can be obtained during the carbonization stage, providing ideal substrate conditions for subsequent surface modification. Stepwise chemical modification with coupling agents and stearic acid constructs a dense and stable chemically bonded layer on the surface of the nano-calcium carbonate, overcoming the defects of incomplete single-layer coating and insufficient interfacial bonding strength in traditional methods. The modified nano-calcium carbonate changes from hydrophilic to hydrophobic, exhibiting high activation and significantly improved interfacial compatibility with the PE matrix. A composite physical lubrication coating of tributyl citrate and PE wax constructs a lubricating outer layer beyond the chemically bonded layer, establishing a dual dispersion mechanism of chemical bonding and physical lubrication. This ensures that the nano-calcium carbonate maintains a uniform nanoscale distribution throughout masterbatch preparation and subsequent film forming, maintaining good melt flow rate and processing fluidity even at high filler levels, avoiding processing difficulties or uneven dispersion caused by excessive filler. Detailed Implementation

[0016] The features and exemplary embodiments of various aspects of the present invention will now be described in detail. In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to specific embodiments.

[0017] In this invention: sodium hexametaphosphate is industrial-grade sodium hexametaphosphate (purity ≥90%), produced by Hubei Xingfa Group; ethylene glycol is industrial-grade ethylene glycol (purity ≥99%), produced by Yanshan Petrochemical Co., Ltd.; lactic acid is industrial-grade lactic acid (purity ≥80%), produced by Henan Xinghan Biotechnology Co., Ltd.; the silane coupling agent selected is KH-550 type (γ-aminopropyltriethoxysilane, purity ≥98%, density 0.940~0.950g / cm³). 3The refractive index is 1.4180~1.4210, produced by Qingdao Xuxin Chemical Co., Ltd.; the titanate coupling agent selected is NDZ-105 type (isopropyltrioleoyloxytitanate, density 0.940~0.960g / cm³). 3 The following materials were selected: stearic acid (1.470–1.480), produced by Nanjing Quanxi Chemical Co., Ltd.; stearic acid (1842 type industrial grade stearic acid, octadecanoic acid, acid value 205–211 mg KOH / g, freezing point 54–57℃), produced by Nantong Kangqiao Oil Co., Ltd.; tributyl citrate (industrial grade tributyl citrate, purity ≥98%, density (20℃) 1.39–1.45 g / mL, refractive index 1.443–1.446), produced by Fujian Huanyang New Materials Co., Ltd.; and PE wax (LW-85 type PE wax, dropping melting point 82–88℃, molecular weight 500–1200, penetration (25℃, 0.1 mm) 10–22, melt viscosity at 140℃ 5. -25 mPa•s), produced by Shandong Shunbang New Material Co., Ltd.; Low-density polyethylene is 2426H type LDPE (melt flow rate (190℃ / 2.16kg) 1.9~2g / 10min), produced by Maoming Petrochemical Co., Ltd.; Antioxidant is 168 type antioxidant (tris(2,4-di-tert-butylphenyl) phosphite, main content ≥99%), produced by Qingdao Jiedejia New Material Co., Ltd.; Zinc stearate is industrial grade zinc stearate (purity ≥99%), produced by Shandong Yukang Chemical Co., Ltd.

[0018] Example 1 S1. Preparation of nano-calcium carbonate powder (1) The limestone was successively crushed, calcined, digested, aged, and filtered to obtain Ca(OH)2 slurry. The specific operations all adopted mature technologies in this field, and the detailed steps are not described in detail. Subsequently, according to the measured solid content, water was added to dilute the Ca(OH)2 slurry to make its mass concentration reach 6%.

[0019] (2) Weigh sodium hexametaphosphate, ethylene glycol and lactic acid in a mass ratio of 1:0.5:0.5, mix them thoroughly, and prepare a mixed crystal form control agent.

[0020] (3) To an effective volume of 1m 3 600L of Ca(OH)2 slurry was pumped into the carbonization reactor, stirring was started, and the system temperature was controlled at 20℃. 0.5% (dry basis weight) of a mixed crystal form control agent was added to the Ca(OH)2 slurry. A CO2 / N2 mixed gas was introduced to carry out the carbonization reaction, with a CO2 to N2 volume ratio of 1:1 and the gas flow rate stably controlled at 36m³. 3 / min.

[0021] (4) Carbonize until the pH of the system drops to 8, stop the gas flow, let it stand at a constant temperature for 40 minutes, and then introduce CO2 / N2 mixed gas for secondary carbonization for 15 minutes to obtain calcium carbonate slurry.

[0022] (5) The calcium carbonate slurry is centrifuged and the solids are collected and then vacuum dried at 80°C to constant weight. The dried blocky powder is deagglomerated by airflow to obtain nano calcium carbonate powder.

[0023] S2, Slurry preparation The nano-calcium carbonate powder obtained in step S1 is added to water and stirred evenly to prepare a slurry with a solid content of 15%. The pH value of the slurry is adjusted to 8 with a 10% NaOH solution to obtain the nano-calcium carbonate slurry.

[0024] S3, Coupling agent dilution Weigh out the silane coupling agent and titanate coupling agent at a mass ratio of 1:1, then add them to anhydrous ethanol and stir until they are evenly mixed to obtain a diluted coupling agent solution.

[0025] The total amount of silane coupling agent and titanate coupling agent is 2% of the mass of nano-calcium carbonate powder, and the amount of anhydrous ethanol is the sum of the volumes of silane coupling agent and titanate coupling agent.

[0026] S4, First Modification The coupling agent dilution was added to the nano-calcium carbonate slurry by spraying, and the addition time was controlled at 40 min. After the addition was completed, the system temperature was raised to 60℃, and the reaction was carried out by stirring for 90 min to complete the first modification.

[0027] S5, Second Modification After the first modification, molten stearic acid was slowly added dropwise to the reaction system. The amount of stearic acid was 2% of the mass of the nano-calcium carbonate powder. The addition time was 15 minutes. After the addition was completed, the mixture was kept warm and stirred for 60 minutes to complete the second modification.

[0028] S6. Separation and Drying After modification, the slurry was naturally cooled to room temperature, centrifuged, and the solids were collected. The solids were washed twice with deionized water and vacuum dried at 80°C to constant weight. The dried blocky powder was then pulverized and passed through a 200-mesh sieve to obtain modified nano-calcium carbonate powder.

[0029] S7, Third Modification Tributyl citrate was added to the modified nano-calcium carbonate powder by spraying, with the amount of tributyl citrate being 1% of the mass of the nano-calcium carbonate powder. The mixture was stirred for 5 minutes, and then PE wax was added, with the amount being 1% of the mass of the nano-calcium carbonate powder. The mixing temperature was 90℃ and the mixing time was 10 minutes to obtain the composite modified nano-calcium carbonate powder.

[0030] S8, Curing process The modified powder was heated to 110℃, kept at a constant temperature for 20 minutes, and then naturally cooled to room temperature. It was then deagglomerated using an air jet mill and passed through a 200-mesh sieve to obtain a high-compatibility modified nano-calcium carbonate powder product.

[0031] Example 2 S1. Preparation of nano-calcium carbonate powder (1) According to the existing process, limestone is successively crushed, calcined, digested, aged and filtered to obtain Ca(OH)2 slurry. Based on the measured solid content, water is added to adjust the mass concentration of Ca(OH)2 slurry to 8%.

[0032] (2) Weigh sodium hexametaphosphate, ethylene glycol and lactic acid in a mass ratio of 2:1:0.75, mix them thoroughly, and prepare a mixed crystal form control agent solution.

[0033] (3) To an effective volume of 1m 3 600L of Ca(OH)2 slurry was pumped into the carbonization reactor, stirring was started, and the system temperature was controlled at 23℃. A CO2 / N2 mixed gas was introduced to carry out the carbonization reaction, with a CO2 to N2 volume ratio of 1:1.5 and the gas flow rate was stably controlled at 40m³ / h. 3 / min.

[0034] (4) Carbonize until the pH of the system drops to 7.5, stop the gas flow, let it stand at a constant temperature for 30 minutes, and then introduce CO2 / N2 mixed gas for secondary carbonization for 10 minutes to obtain calcium carbonate slurry.

[0035] (5) After secondary carbonation, the calcium carbonate slurry is centrifuged and the solids are collected and then vacuum dried at 80°C to constant weight. The dried blocky powder is deagglomerated by airflow to obtain nano calcium carbonate powder.

[0036] S2, Slurry preparation The nano-calcium carbonate powder obtained in step S1 is added to water and stirred evenly to prepare a slurry with a solid content of 30%. The pH value of the slurry is adjusted to 8.5 with a 10% NaOH solution to obtain the nano-calcium carbonate slurry.

[0037] S3, Coupling agent dilution A composite coupling agent, which is a mixture of silane coupling agent and titanate coupling agent at a mass ratio of 1:1.5, is added to two times its volume of anhydrous ethanol and stirred until completely dissolved to obtain a diluted coupling agent solution. The total amount of the composite coupling agent is 3% of the mass of the nano-calcium carbonate powder.

[0038] S4, First Modification The coupling agent dilution was added to the nano-calcium carbonate slurry by spraying, and the addition time was controlled at 30 minutes. After the addition was completed, the system temperature was raised to 70°C and the mixture was kept at this temperature and stirred for 60 minutes to complete the first modification.

[0039] S5, Second Modification After the first modification, molten stearic acid was slowly added dropwise to the reaction system. The amount of stearic acid was 3% of the mass of the nano-calcium carbonate powder. The addition time was 20 minutes. After the addition was completed, the mixture was kept warm and stirred for 50 minutes to complete the second modification.

[0040] S6. Separation and Drying After modification, the slurry was naturally cooled to room temperature, centrifuged, and the solids were collected. The solids were washed twice with deionized water and vacuum dried at 80°C to constant weight. The dried blocky powder was then pulverized and passed through a 200-mesh sieve to obtain modified nano-calcium carbonate powder.

[0041] S7, Third Modification Tributyl citrate was added to the modified nano-calcium carbonate powder by spraying. The amount of tributyl citrate was 2% of the mass of the nano-calcium carbonate powder. The mixture was stirred for 10 minutes. Then, PE wax was added. The amount of PE wax was 3% of the mass of the nano-calcium carbonate powder. The mixing temperature was 95℃ and the mixing time was 10 minutes to obtain the composite modified nano-calcium carbonate powder.

[0042] S8, Curing process The modified powder was heated to 120℃, kept at a constant temperature for 30 minutes, and then naturally cooled to room temperature. It was then deagglomerated using an air jet mill and passed through a 200-mesh sieve to obtain a high-compatibility modified nano-calcium carbonate powder product.

[0043] Example 3 S1. Preparation of nano-calcium carbonate powder (1) According to the existing process, limestone is crushed, calcined, digested, aged and filtered in sequence to obtain Ca(OH)2 slurry. Based on the measured solid content, water is added to adjust the mass concentration of Ca(OH)2 slurry to 10%.

[0044] (2) Weigh sodium hexametaphosphate, ethylene glycol and lactic acid in a mass ratio of 3:1.5:1, mix them thoroughly, and prepare a mixed crystal form control agent solution.

[0045] (3) To an effective volume of 1m 3 600L of Ca(OH)2 slurry was pumped into the carbonization reactor, stirring was started, and the system temperature was controlled at 30℃. A CO2 / N2 mixed gas was introduced to carry out the carbonization reaction, with a CO2 to N2 volume ratio of 1:2 and the gas flow rate was stably controlled at 48m³ / h. 3 / min.

[0046] (4) Carbonize until the pH of the system drops to 7, stop the gas flow, let it stand at a constant temperature for 20 minutes, and then introduce CO2 / N2 mixed gas for secondary carbonization for 5 minutes to obtain calcium carbonate slurry.

[0047] (5) After secondary carbonation, the calcium carbonate slurry is centrifuged and the solids are collected and then vacuum dried at 80°C to constant weight. The dried blocky powder is deagglomerated by airflow to obtain nano calcium carbonate powder.

[0048] S2, Slurry preparation The nano-calcium carbonate powder obtained in step S1 is added to water and stirred evenly to prepare a slurry with a solid content of 40%. The pH value of the slurry is adjusted to 9 with a 10% NaOH solution to obtain the nano-calcium carbonate slurry.

[0049] S3, Coupling agent dilution A composite coupling agent, prepared by mixing silane coupling agent and titanate coupling agent at a mass ratio of 1:2, was added to three times its volume of anhydrous ethanol and stirred until completely dissolved to obtain a diluted coupling agent solution. The total amount of the composite coupling agent used was 3.5% of the mass of the nano-calcium carbonate powder.

[0050] S4, First Modification The coupling agent dilution was added to the nano-calcium carbonate slurry by spraying, and the addition time was controlled at 20 minutes. After the addition was completed, the system temperature was raised to 80°C, and the mixture was kept at this temperature and stirred for 80 minutes to complete the first modification.

[0051] S5, Second Modification After the first modification, molten stearic acid was slowly added dropwise to the reaction system. The amount of stearic acid was 4% of the mass of the nano-calcium carbonate powder. The addition time was 30 minutes. After the addition was completed, the mixture was kept warm and stirred for 55 minutes to complete the second modification.

[0052] S6. Separation and Drying After modification, the slurry was naturally cooled to room temperature, centrifuged, and the solids were collected. The solids were washed twice with deionized water and vacuum dried at 80°C to constant weight. The dried blocky powder was then pulverized and passed through a 200-mesh sieve to obtain modified nano-calcium carbonate powder.

[0053] S7, Third Modification Tributyl citrate was added to the modified nano-calcium carbonate powder by spraying. The amount of tributyl citrate was 3% of the mass of the nano-calcium carbonate powder. The mixture was stirred for 15 minutes. Then, PE wax was added. The amount of PE wax was 5% of the mass of the nano-calcium carbonate powder. The mixing temperature was 100℃ and the mixing time was 30 minutes to obtain the composite modified nano-calcium carbonate powder.

[0054] S8, Curing process The modified powder was heated to 130℃, kept at a constant temperature for 60 minutes, and then naturally cooled to room temperature. It was then deagglomerated using an air jet mill and passed through a 200-mesh sieve to obtain a high-compatibility modified nano-calcium carbonate powder product.

[0055] Comparative Example 1 Based on Example 2, a silane coupling agent was added to twice its volume of anhydrous ethanol and stirred until completely dissolved to obtain a diluted coupling agent solution. The amount of silane coupling agent was 2.8% of the mass of the nano-calcium carbonate powder. The diluted coupling agent solution was added to the nano-calcium carbonate slurry in the form of a spray, and the addition time was controlled at 30 min. After the addition was completed, the system temperature was raised to 70°C and the mixture was kept at this temperature and stirred for 75 min to complete the modification. After drying, the mixture was depolymerized by an air jet mill and passed through a 200-mesh sieve to obtain the finished nano-calcium carbonate powder product modified only by the silane coupling agent.

[0056] The highly compatible nano-calcium carbonate powder products obtained in Examples 1-3 and Comparative Example 1 were used to prepare PE toughening masterbatches, and the specific methods are as follows.

[0057] Weigh the following raw materials by weight: 60 parts of highly compatible nano-calcium carbonate powder, 40 parts of low-density polyethylene, 0.2 parts of antioxidant and 0.1 parts of zinc stearate.

[0058] The above raw materials were mixed in a high-speed mixer at 100°C for 15 minutes, and then fed into a twin-screw extruder for melt blending and extrusion. The temperatures of each section of the extruder were set as follows: feeding section 150°C, melting section 170°C, mixing section 180°C, homogenizing section 175°C, and die head 170°C. The screw speed was 200 r / min. The extrudate was cooled in a water bath, pelletized, and vacuum dried at 80°C for 4 hours to obtain PE toughening masterbatch.

[0059] The above masterbatch was mixed with pure low-density polyethylene at a mass ratio of 30:70, and then blown into a film by single screw extrusion to obtain a film sample with a thickness of about 40 μm, which was used for puncture resistance testing.

[0060] In the mechanical property tests, tensile strength, elongation at break, and yield strength were tested according to GB / T1040.3-2006 on a universal testing machine (INSTRON, USA) at room temperature; puncture resistance was tested according to GB / T37841-2019 using a universal testing machine (SHK-A102 type) with a special puncture clamp; transmittance was tested according to GB / T2410-2008 using a WGT-S type transmittance and haze meter (Jinan Langguang) with a C light source; and UV aging resistance was tested according to GB / T14522-2008 using a QUV / se type fluorescent UV aging tester (Q-LAB, USA) with a UVA-340 lamp.

[0061] Table 1 Performance Test Table

[0062] As shown in Table 1, Comparative Example 1 only used a single modification with a silane coupling agent, without chemical supplementation with stearic acid or physical lubrication composite coating with tributyl citrate and PE wax, in order to compare the synergistic effect of the composite coupling agent and stepwise chemical modification of the present invention. As a result, the surface polarity of the nano-calcium carbonate was not fully transformed. Under high filling conditions, the nano-calcium carbonate of Comparative Example 1 was severely agglomerated in the PE matrix. Its film tensile strength, elongation at break, yield strength, puncture resistance, transmittance and UV aging resistance were significantly inferior to those of the other examples.

[0063] In Examples 1-3, a complete dual dispersion mechanism of chemical bonding and physical lubrication was constructed by employing a three-stage synergistic technical scheme involving crystal form control, chemical bonding modification, physical lubrication coating, and so on. Among them, Example 2 exhibited the best overall performance, demonstrating that even with high filling amounts, uniform dispersion of nano-calcium carbonate can still be achieved while maintaining good processing fluidity and toughening effects.

Claims

1. A method for preparing highly compatible nano-calcium carbonate, characterized in that, Includes the following steps: S1. Limestone is crushed, calcined, digested, aged, and filtered to obtain Ca(OH)2 slurry; S2. Pump Ca(OH)2 slurry into the carbonization kettle, add crystal form control agent, start stirring, control the temperature at 20-30℃, and introduce CO2 / N2 mixed gas to carry out carbonization reaction. The crystal form control agent is composed of sodium hexametaphosphate, ethylene glycol and lactic acid. S3. Carbonize until the pH of the system drops to 7-8, stop the gas supply, let it stand at a constant temperature for 20-40 minutes, and then carry out a second carbonization for 5-15 minutes to obtain calcium carbonate slurry. S4. After the calcium carbonate slurry has been aged, it is centrifuged and the solids are collected and then vacuum dried. The dried blocky powder is deagglomerated by airflow to obtain nano-calcium carbonate powder. S5. Add nano-calcium carbonate powder to water, stir and mix to prepare a slurry with a solid content of 15% to 40%, and adjust the pH value of the slurry to 8 to 9 with NaOH aqueous solution to obtain nano-calcium carbonate slurry; S6. Add the coupling agent to 1 to 3 times its volume of anhydrous ethanol, stir and mix to obtain a diluted coupling agent solution; S7. Add the prepared coupling agent dilution to the nano-calcium carbonate slurry in the form of a spray. The addition time is controlled at 20-40 minutes. After the addition is completed, raise the system temperature to 60-80℃ and keep it at the temperature while stirring for 60-90 minutes to complete the first modification. S8. After the first modification is completed, slowly add molten stearic acid dropwise into the reaction system over a period of 15 to 30 minutes. After the addition is complete, keep the mixture warm and stir for 50 to 60 minutes to complete the second modification. S9. After the modification is completed, the slurry is naturally cooled to room temperature, centrifuged, the solids are collected, washed and dried, and the dried block powder is crushed and sieved to obtain modified nano calcium carbonate powder. S10. Add tributyl citrate to the modified nano-calcium carbonate powder in the form of spray, stir and mix for 5 to 15 minutes, add PE wax, mix at a temperature of 90 to 100°C for 10 to 30 minutes to obtain composite modified nano-calcium carbonate powder. S11. The modified powder is heated to 110-130℃ and cured at a constant temperature for 20-60 minutes. It is then naturally cooled to room temperature, deagglomerated by an air jet mill, and sieved to obtain a highly compatible modified nano-calcium carbonate product.

2. The method for preparing highly compatible nano-calcium carbonate according to claim 1, characterized in that: The coupling agent is a composite coupling agent composed of silane coupling agent and titanate coupling agent in a mass ratio of 1:1 to 2, and the total amount of the composite coupling agent is 2% to 3.5% of the mass of the nano-calcium carbonate powder.

3. The method for preparing highly compatible nano-calcium carbonate according to claim 1, characterized in that: The amount of stearic acid used is 2% to 4% of the mass of the nano-calcium carbonate powder.

4. The method for preparing highly compatible nano-calcium carbonate according to claim 1, characterized in that: The amount of tributyl citrate used is 1% to 3% of the mass of the nano-calcium carbonate powder, and the amount of PE wax used is 1% to 5% of the mass of the nano-calcium carbonate powder.

5. The method for preparing highly compatible nano-calcium carbonate according to claim 1, characterized in that: The crystal form control agent is composed of sodium hexametaphosphate, ethylene glycol, and lactic acid in a mass ratio of 1-3:0.5-1.5:0.5-1, and the total amount of the crystal form control agent is 0.5%-3.5% of the dry basis mass of the Ca(OH)2 slurry.

6. The method for preparing highly compatible nano-calcium carbonate according to claim 1, characterized in that: The volume ratio of CO2 to N2 in the CO2 / N2 mixed gas is 1:1 to 2.

7. The method for preparing highly compatible nano-calcium carbonate according to claim 6, characterized in that: The total ventilation flow rate of the CO2 / N2 mixed gas was stably controlled at 36–48 m³ / h. 3 / min.

8. The method for preparing highly compatible nano-calcium carbonate according to claim 1, characterized in that: The mass concentration of the Ca(OH)2 slurry is 6% to 10%.

Citation Information

Patent Citations

  • Method for modifying ultrafine light calcium carbonate and application of ultrafine light calcium carbonate in plastics

    CN107629487A

  • Preparation method of nano calcium carbonate

    CN116477653A